2000
DOI: 10.1038/sj.bjp.0703491
|View full text |Cite
|
Sign up to set email alerts
|

Functional, biochemical and molecular biological evidence for a possible β3‐adrenoceptor in human near‐term myometrium

Abstract: 1 The possible existence of a b 3 -adrenoceptor (b 3 -AR) in human near-term myometrium was investigated by in vitro functional and biochemical studies and analysis of mRNA expression. 2 SR 59119A and SR 59104A and CGP 12177 (two selective agonists and a partial agonist, respectively, of the b 3 -AR), salbutamol and terbutaline (b 2 -AR agonists) each produced a concentration-dependent relaxation of the myometrial spontaneous contractions. There were no di erences in pD 2 values for the relaxing potencies of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 47 publications
3
44
0
Order By: Relevance
“…In our experimental conditions, we confirmed that, without pretreatment of the myometrial strips, both salbutamol and SR 59119A were able to inhibit spontaneous contractions and to induce cAMP production. These findings provide confirmation of b 2 -and b 3 -AR functional integrity, and positive coupling with the adenylyl cyclase pathway (Bardou et al, 2000). Our functional and biochemical results demonstrate that b 2 -AR undergoes functional desensitisation after long-term exposure to salbutamol, which is associated with a significant decrease in cAMP production.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…In our experimental conditions, we confirmed that, without pretreatment of the myometrial strips, both salbutamol and SR 59119A were able to inhibit spontaneous contractions and to induce cAMP production. These findings provide confirmation of b 2 -and b 3 -AR functional integrity, and positive coupling with the adenylyl cyclase pathway (Bardou et al, 2000). Our functional and biochemical results demonstrate that b 2 -AR undergoes functional desensitisation after long-term exposure to salbutamol, which is associated with a significant decrease in cAMP production.…”
Section: Discussionsupporting
confidence: 78%
“…We previously determined that maximal effects of salbutamol and SR 59119A were obtained at the concentration of 10 mM (Bardou et al, 2000).…”
Section: Tissue Incubation Processmentioning
confidence: 99%
See 3 more Smart Citations